Silica nanoparticles induce reversible damage of spermatogenic cells via RIPK1 signal pathways in C57 mice - Ren L (Dove Medical Press, 2016)
Lihua Ren,1,2 Jin Zhang,1,2 Yang Zou,1,2 Lianshuang Zhang,1,2 Jialiu Wei,1,2 Zhixiong Shi,1,2 Yanbo Li,1,2 Caixia Guo,2 Zhiwei Sun,1,2 Xianqing Zhou1,21Department of Toxicology and Hygienic Chemistry, School of Public Health, 2Beijing Key Laboratory of Environmental Toxicology, Capital Medical University, Beijing, People’s Republic of ChinaAbstract: The reproductive toxicity of silica nanoparticles (SiNPs) is well known, but the underlying mechanism is still not clear. To investigate the toxic mechanism of SiNPs on spermatogenic cells, 60 C57 male mice were randomly and equally divided into three groups (the control group, the saline control group, and the SiNPs group) with two observed time points (45 days and 75 days). The mice in the SiNPs group were administered with SiNPs 2 mg/kg diluted in normal saline, and the mice of the saline control group were given equivoluminal normal saline by tracheal perfusion every 3 days for 45 days (in total 15 times). The control group mice were bred without treatment. In each group, a half number of the mice were sacrificed on the 45th day after the first dose, and the remaining half were sacrificed on the 75th day. The results showed that SiNPs increased the malformation of sperms and decreased the motility and concentration of sperms in epididymis on the 45th day after the first dose. SiNPs induced oxidative stress in testis and led to apoptosis and necroptosis of the spermatogenic cells. Furthermore, SiNPs increased the expression of Fas/FasL/RIPK1/FADD/caspase-8/caspase-3 and RIPK3/MLKL on the 45th day after the first dose. However, compared with the saline control group, the index of sperms and the expression of Fas/FasL/RIPK1/FADD/caspase-8/caspase-3/RIPK3/MLKL showed no significant changes in the SiNPs group on the 75th day after the first dose. These data suggested that SiNPs could induce apoptosis and necroptosis in the spermatogenic cells by activating the RIPK1 pathway resulting from oxidative stress in male mice. SiNPs-induced damage recovered on the 75th day after the first dose, which suggested that SiNPs-induced toxicity is reversible.Keywords: silica nanoparticles, RIPK1 signal pathway, apoptosis, necroptosis, spermatogenic cells, reversible